This wounded land; the era of Reconstruction, 1865-1877. - Werstein, Irving (New York, Delacorte Press, 1968)
Briefly examines slavery in the South before and during the Civil War; then appraises the social and political situation during the years following the conflict, describing Lincoln's plans, Johnson's policies, Grant's administration, and Hayes' election.
Bibliography: p. [169]-170.
Keywords: Reconstruction (U.S. history, 1865-1877) -- Juvenile literature; Reconstruction (U.S. history, 1865-1877)